Development of a Portable Digital Fetal Heart Rate Monitoring System Using Ultrasonic Echo Doppler Method - Lusiana; Ridha Mak’ruf, Muhammad; Nashichah, Roichatun (Medika Teknika : Jurnal Teknik Elektromedik Indonesia, 2026)
This research aims to monitor the fetal heart rate (DJJ) using the ultrasonic echo method by detecting the fetal heartbeat at a certain tissue depth. The ultrasonic echo method used in this study is non-invasive and easy to use. The developed system consists of a 2.5 MHz piezoelectric probe that functions to transmit and receive ultrasonic signals, an Arduino that functions for signal processing and a program used to display the fetal heartbeat output. This ultrasonic echo method can detect the fetal heartbeat accurately and timely. This research produces outputs in the form of an Accredited National Journal and Intellectual Property Rights. The study contributes to the advancement of more sophisticated and user-friendly prenatal monitoring technology, in accordance with Technology Readiness Level (TRL) 2. By employing the Ultrasonic Echo method, this system offers convenience in FHR monitoring, potentially improving prenatal care and ensuring optimal fetal health.